2019
DOI: 10.1007/s10911-018-09423-x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Association between Mammographic Density and Gene Expression in Normal Breast Tissue

Abstract: High mammographic density (MD) is associated with a 4-6 times increase in breast cancer risk. For post-menopausal women, MD often decreases over time, but little is known about the underlying biological mechanisms. MD reflects breast tissue composition, and may be associated with microenvironment subtypes previously identified in tumor-adjacent normal tissue. Currently, these subtypes have not been explored in normal breast tissue. We obtained biopsies from breasts of healthy women at two different time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…46 Furthermore, the "active" signature can change over time and location in nonaffected breast tissue, suggestive of an immune-or stromal-related change. 47 Our results suggest that perhaps IL-4 and IL-13 either directly or more likely indirectly through polarization of macrophages toward M2 alter the microenvironment to cause the "active" phenotype. Stromal responses likely perpetuate the progression of breast cancer, especially if a premalignant lesion is present, and it is therefore imperative to take advantage of complex model systems that allow us to investigate how varying stimuli can modify both stromal and epithelial responses.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…46 Furthermore, the "active" signature can change over time and location in nonaffected breast tissue, suggestive of an immune-or stromal-related change. 47 Our results suggest that perhaps IL-4 and IL-13 either directly or more likely indirectly through polarization of macrophages toward M2 alter the microenvironment to cause the "active" phenotype. Stromal responses likely perpetuate the progression of breast cancer, especially if a premalignant lesion is present, and it is therefore imperative to take advantage of complex model systems that allow us to investigate how varying stimuli can modify both stromal and epithelial responses.…”
Section: Discussionmentioning
confidence: 71%
“…More recent publications have revealed that even normal tissue from women without cancer can be classified into “active” versus “inactive” and correlates with adiposity 46 . Furthermore, the “active” signature can change over time and location in nonaffected breast tissue, suggestive of an immune‐ or stromal‐related change 47 . Our results suggest that perhaps IL‐4 and IL‐13 either directly or more likely indirectly through polarization of macrophages toward M2 alter the microenvironment to cause the “active” phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin-low tumors had high levels of non-tumor cell infiltration, and there was a lower prevalence of claudin-low tumors in the cohorts with a cut-off for tumor cellularity. It is also known that EMT-like gene expression features in tumors are similar to the gene expression characteristics of stromal tissue 29 , and a subset of normal breast tissue samples show marked similarities to claudin-low-like gene expression patterns 30,31 . In the context of these observations, it is pertinent to ask: How much of the claudin-low phenotype is a result of stromal infiltration, and could the claudin-low phenotype simply be an artifact of stromal infiltration?…”
Section: Discussionmentioning
confidence: 96%
“…3). This can be related to the marked stromal and immune infiltration in claudin-low tumors 12 , and to the partial overlap in gene expression features between stromal tissue and tumors with an EMT phenotype [29][30][31] . Given these challenges which arose from the unbiased approach used by Prat et al 12 , and the progress made in the understanding of claudin-low tumors 6,14,15,32 , we chose to explore a biased approach to identifying claudin-low tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Such tissue samples often show more histological abnormalities when compared to tissue obtained from healthy donors, 9–11 and using different sources of control breast tissue in different studies make comparisons between studies difficult. In addition, most studies on gene expression profiles were generated from a small set of samples that were likely not representative of the general population 8,12 . Finally, a better understanding of the natural variability of gene expression in normal breast tissue would represent a significant step forward in our understanding of early disease‐related mechanisms.…”
Section: Introductionmentioning
confidence: 99%